Penggunaan Katekese Digital bagi Pendidikan Iman Anak Usia Dini - Petriana Dae Lelangwayan; Intansakti Pius X (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
The development of digital technology has brought about significant changes in various aspects of life, including early childhood faith education. Today’s children are growing up in an environment familiar with digital media, making it necessary to adopt a catechetical approach that keeps pace with the times. This article aims to examine the use of digital catechesis as a tool for early childhood faith education. This study employs a qualitative method with a literature review approach, gathering data from books, scientific journals, research articles, Church documents, and other relevant sources. The data is analyzed using descriptive-qualitative methods to understand the benefits, challenges, and role of digital catechesis in fostering children’s faith. Research findings indicate that digital catechesis can serve as an effective, engaging, and interactive medium for helping children learn about the teachings of the faith from an early age. The use of animated videos, religious songs, educational images, and learning apps can enhance children’s interest in learning, attention, and understanding of Catholic faith values. Furthermore, digital catechesis also assists the Church, families, and schools in providing faith education that is more contextual and aligned with the world of today’s children. However, the use of digital media still requires the guidance of parents, teachers, and faith mentors so that children receive proper direction and are protected from the negative impacts of technology. Thus, digital catechesis is a relevant tool in the faith education of young children when used wisely and purposefully. The presence of digital media does not replace the role of faith educators but serves as a tool that enriches the process of proclaiming the faith in the modern era.